2004
DOI: 10.1016/j.devcel.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-Epithelial Transition during Somitic Segmentation Is Regulated by Differential Roles of Cdc42 and Rac1

Abstract: Mesenchymal-epithelial transitions (MET) are crucial for vertebrate organogenesis. The roles of Rho family GTPases in such processes during actual development remain largely unknown. By electroporating genes into chick presomitic mesenchymal cells, we demonstrate that Cdc42 and Rac1 play important and different roles in the MET that generates the vertebrate somites. Presomitic mesenchymal cells, which normally contribute to both the epithelial and mesenchymal populations of the somite, were hyperepithelialized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
148
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 152 publications
(154 citation statements)
references
References 60 publications
2
148
0
4
Order By: Relevance
“…Interestingly, although Xenopus somites undergo a 90-degree rotation but do not epithelialize, time-lapse analyses showed that individual cells bend in a precise spatiotemporal manner that propagates in a dorsal-to-ventral direction (Afonin et al, 2006). In a similar manner, in analysis of histological sections from the chick PSM (Duband et al, 1987;Sato et al, 2002;Nakaya et al, 2004), the presumptive posterior border, including the dorsal, ventral, medial, and lateral sleeves of the new somite, appear epithelialized. Sato and Takahashi (2005) later revealed that the ventral-to-dorsal propagation of tissue separation is accompanied by an epithelial morphology of cells along the somite border.…”
Section: Targeting Somite Epithelializationmentioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, although Xenopus somites undergo a 90-degree rotation but do not epithelialize, time-lapse analyses showed that individual cells bend in a precise spatiotemporal manner that propagates in a dorsal-to-ventral direction (Afonin et al, 2006). In a similar manner, in analysis of histological sections from the chick PSM (Duband et al, 1987;Sato et al, 2002;Nakaya et al, 2004), the presumptive posterior border, including the dorsal, ventral, medial, and lateral sleeves of the new somite, appear epithelialized. Sato and Takahashi (2005) later revealed that the ventral-to-dorsal propagation of tissue separation is accompanied by an epithelial morphology of cells along the somite border.…”
Section: Targeting Somite Epithelializationmentioning
confidence: 94%
“…The Rho family of small GTPases, including Cdc42 and Rac1, mediate the necessary forces for changes of polarity, motility, and structural stability of the cell (Etienne-Manneville, 2004). It has been shown recently in chick that when Cdc42 is overexpressed in the PSM, cells remain mesenchymal (Nakaya et al, 2004). In contrast, when inhibition of endogenous Cdc42 is performed by overexpression of the CRIB domain of N-WASP, cells in the PSM are hyperepithelialized (Nakaya et al, 2004).…”
Section: Targeting Somite Epithelializationmentioning
confidence: 99%
See 1 more Smart Citation
“…1B). This is an example of a mesenchymal-epithelial transition (MET) as paraxial mesoderm organizes into epithelialized somites (Nakaya et al, 2004). Expression was also seen in the notochord and the nephric ducts at this stage ( Fig.…”
Section: Expression Analysis Of Latrophilin-2 At the Time Of Emtmentioning
confidence: 82%
“…In addition, MesP2 requires Notch signals to start its expression in PSM (5), and Notch activation is sufficient for the formation of an ectopic gap (1). Furthermore, when the MET occurs concomitantly with the gap formation, the Rhofamily member Cdc42 is known to be critical for the epithelialization of cells that are juxtaposed to the forming gap (6). In this study we have clarified the molecular cascade originating from the MesP gene in posterior border cells to the Cdc42-mediated MET of anterior border cells through intercellular signaling.…”
mentioning
confidence: 87%